STAPHYLOCOCCUS SPP. BACTERIA IN KOI FISH REARED DURING QUARANTINE PERIOD - Fairizca, Syafiana; Mahatmi, Hapsari; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana, 2022)
Currently, koi fish enthusiasts and fans in various regions in Indonesia, especially in Bali, have increased very sharply. In the conditions of transportation from outside Bali to Bali, it triggers stress which causes the koi's resistance to decrease so that disease occurs. Therefore, a quarantine process is very necessary to get koi that are healthy and suitable for cultivation. Diseases in koi fish can be caused by viruses, parasites, and bacteria, one of which is Staphylococcus s p p. Research on bacterial infections in koi fish is still very rare, especially regarding Staphylococcus sp p. in koi fish in Indonesia and in Bali. This study was conducted to obtain preliminary data regarding Staphylococcus sp infection in koi fish. In this study, the object used was koi fish which has any symptomps of diseases or died during a 14-day quarantine period.The researched koi fish came from suppliers in Tulungagung and Blitar, East Java. The size of the koi fish ranged from 15 -25 cm which was kept in fish isolation ponds at Raka koi and Tilapia Farm, Denpasar. The samples taken were 19 samples, the 8 samples are thescale swabs from koi fish from Tulungagung and 11 scale swab samples from koi fish from Blitar using random sampling technique. Staphylococcus sp was isolated with Blood Agar and MacConkey Agar media and identified by Gram stain test and catalase test. From the results of the isolation and identification of bacteria, 1 sample was positive for Staphylococcus sp p. (5.26%).